Production in Entrepreneurial Firms: The Effects of Financial Constraints on Labor and Capital - Garmaise, Mark J. (Review of Financial Studies, 2008)
I model the contrasting capital-labor decisions of financially constrained and unconstrained firms. I show that financially restricted firms use relatively more labor than physical capital because informed employees provide more efficient financing than uninformed capital suppliers. I demonstrate that constrained firms cannot easily attract new employees to replace existing staff. Their greater employee retention aligns owner-worker incentives and encourages workers to make firm-specific investments. Constrained firms, however, gradually suffer from their inability to replace low-quality workers, such that their relative labor productivity decreases over time. Empirical tests utilizing instrumental variables confirm several implications of the theory. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.